Every man a king - Mosley, Walter (Mosley, Walter. King Oliver novel, 2023)
After being asked to investigate the charges against a white nationalist accused of treason and murder, Joe King Oliver, with help from bodyguard and mercenary Oliya Ruez, embarks on a winding quest to expose the truth.